RESPONSABILIZAÇÃO CIVIL DO AGRESSOR E O DANO EXISTENCIAL DECORRENTE DE VIOLÊNCIA DOMÉSTICA E FAMILIAR: efetividade na aplicação da Lei Maria da Penha no Brasil - LEITE, José Augusto Sá Costa (2021)
The present work aims to address the incidence of existential damage resulting from domestic and family violence focused on its civil reparability. The idea is anchored on the premise that the punitive-penal model is not sufficient to, in isolation, adequately safeguard the fundamental rights of women, because, over the years, it has failed to stop the present violence and prevent future occurrences. The central theme of the research is, therefore, the civil liability of the aggressors, due to the practice of existential damage, as a contribution to the effectiveness of judicial protection exercised in the cases of women in situations of domestic and family violence. More specifically, the understanding of the court of justice of the State of Maranhão is evaluated, with regard to the occurrence of the phenomenon of existential damage in the context of the relationships in which women are victimized by this type of violence. It seeks to answer the following questions: within the scope of civil actions for compensation, it is possible for the Judiciary to exercise effective protection of the human rights of women in situations of domestic and family violence, as victims of existential damage, through civil liability of the aggressor? What has been the perception of the TJMA regarding the repercussions of this type of violence beyond the criminal response? From this perspective, the intention is to make the system of protection of women in situations of domestic and family violence effective, presenting legal instruments that can work together with the protection of the criminal aspect conferred by the Maria da Penha Law. The method applied was that of hypothetical deductive, based on qualitative research, of an exploratory nature, combined with a wide bibliographic review. Likewise, documents collected from the TJMA website were selected and analyzed using the content analysis technique.